ANALISIS IMPLEMENTASI DISIPLIN KERJA DALAM UPAYA MENINGKATKAN KINERJA PEGAWAI PADA KANTOR BUPATI BIDANG EKONOMI DAN SUMBERDAYA ALAM KAB.ACEH SINGKIL - Septami Ayu Lestari; Sri Sudiarti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research aims to analyze the application of discipline in improving employee performance in the economic and natural resources section of the Aceh Singkil Regent's office. The research method used is descriptive qualitative research using sampling techniques in the office, namely 9 employees. This research uses direct observation and interviews with employees inside. From the results of this research, it can be shown that the discipline applied by employees of the Economics and Natural Resources section of the Aceh Singkil Regent's office is the application of preventive discipline such as being on time for work, dressing according to the schedule and carrying out tasks according to predetermined sections that can be carried out. . This shows that the application of this discipline can increase the effectiveness and efficiency of employee performance at work so that they can work optimally. This research also shows that employee performance will increase if employees are able to carry out work discipline in accordance with the regulations stated in the Economics and Natural Resources section of the Aceh Singkil Regent's office.